2014
DOI: 10.1111/ecin.12187
|View full text |Cite
|
Sign up to set email alerts
|

Norms of Punishment: Experiments With Students and the General Population

Abstract: Norms of cooperation and punishment differ across societies, but also within a single society. In an experiment with two subject pools sharing the same geographical and cultural origins, we show that opportunities for peer punishment increase cooperation among students but not in the general population. In previous studies, punishment magnified the differences across societies in people's ability to cooperate. Here, punishment reversed the order: with punishment, students cooperate more than the general popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 59 publications
5
13
0
Order By: Relevance
“…In line with the findings of Bortolotti et al [69], who reported considerable antisocial punishment behavior among Italian subjects, our behavioral results showed that player C punished fair behavior in the out-group condition more often when players A and B, both belonged to the out-group, as compared to when player A belonged to the out-group and player B to the in-group. These results might suggest a form of protection across in-group members, another possible explanation is that our task and experimental procedure may have evoked this competitive behavior in-group setting.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the findings of Bortolotti et al [69], who reported considerable antisocial punishment behavior among Italian subjects, our behavioral results showed that player C punished fair behavior in the out-group condition more often when players A and B, both belonged to the out-group, as compared to when player A belonged to the out-group and player B to the in-group. These results might suggest a form of protection across in-group members, another possible explanation is that our task and experimental procedure may have evoked this competitive behavior in-group setting.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with similar findings in the literature (for a recent review and a methodological discussion see, e.g., [39]). For instance, using a public good game, Gächter and Herrmann [40] show that students are less prosocial than rural and urban citizens, and Cardenas [41] shows that they extract more resources than rural villagers in a common pool resources experiment.…”
Section: Discussionsupporting
confidence: 93%
“…In both cases, cooperation decreases over time in these fixed partner experiments without punishment. With punishment, Bortolotti, Casari, and Pancotto () show that cooperation stays flat in the general population sample but increases slightly among students because students more actively used punishments. Our study contributes to the literature of finitely repeated games with nonstudent subjects by adding evidence on comparative experimental play by Mongolian small business owners versus Mongolian university students.…”
Section: Literature and Hypothesesmentioning
confidence: 99%